2009
DOI: 10.1002/chem.200802572
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanistic Aspects of the Fenton Reaction

Abstract: The kinetics of the Fenton reaction was studied in detail. A second reaction step in the presence of excess H2O2 is attributed to formation of the complex Fe(III)(-O2H)(aq). Therefore, the reaction of Fe(H2O)(6)(2+) with Fe(III)(-O2H)(aq) in the presence of Fe(II) to form Fe(III)(aq) (k=(7.7+/-1.5) x 10(5) M(-1) s(-1)) may contribute to the overall Fenton reaction, and could account for some of the debate in the literature concerning its detailed mechanism. If this is correct for LFe(III)(-O2H)(aq) also, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 60 publications
1
76
1
Order By: Relevance
“…This reaction leads to CH 4 , ethane (C 2 H 6 ), methanol and/or formaldehyde, depending on the reaction conditions [26][27][28][29] . However, under conditions used in our experiments (iron(II/III), ASC and H 2 O 2 ), when FH is replaced by water-soluble iron salts that are believed to produce hydroxyl radicals (Fenton's reaction), very little CH 4 production was observed (o1%; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction leads to CH 4 , ethane (C 2 H 6 ), methanol and/or formaldehyde, depending on the reaction conditions [26][27][28][29] . However, under conditions used in our experiments (iron(II/III), ASC and H 2 O 2 ), when FH is replaced by water-soluble iron salts that are believed to produce hydroxyl radicals (Fenton's reaction), very little CH 4 production was observed (o1%; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The trends of the optical density and COD decreases were nearly identical, which suggested that the decoloration of MB was mainly due to the complete oxidation of MB into CO2 [20][21][22][23][24][25]. Generally, many Fenton systems generate oxidative radicals and other non-radical species [26]. To confirm the existence of ·OH radicals in the FTCNC-H 2 O 2 Fenton-like system, the electron spin resonance (ESR) spectra of the FTCNC-H 2 O 2 Fenton-like system were recorded [21].…”
Section: Decoloration Of Mb In the Ftcnc-h 2 O 2 Fenton-like Systemmentioning
confidence: 88%
“…Beyond the radical process, according to the literature, there might also be non-radical processes involved. Generally, many Fenton systems generate oxidative radicals and other non-radical species [26]. To confirm the existence of •OH radicals in the FTCNC-H2O2 Fenton-like system, the electron spin resonance (ESR) spectra of the FTCNC-H2O2 Fenton-like system were recorded [21].…”
Section: Decoloration Of Mb In the Ftcnc-h 2 O 2 Fenton-like Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ubiquitous and an important source of reactive oxygen species (ROS), if HO • is indeed produced, the identity of the intermediate formed in this reaction has long been the subject of debate (Goldstein et al, 1993;MacFaul et al, 1998;Walling, 1998;Goldstein and Meyerstein, 1999;Dunford, 2002;Rachmilovich-Calis et al, 2009a;Remucal Keenan and Sedlak, 2011). It is generally accepted that HO • is formed under acidic conditions and in the absence of ligands.…”
Section: Introductionmentioning
confidence: 99%